Plasma Nesfatin-1 and Leptin in pubertal and non-pubertal Murrah buffalo heifers (Bubalus bubalis) - Prajapati, Gorakh Nath; Laxmi, N. Anand (Journal of Advanced Veterinary and Animal Research, 2015)
Buffaloes mostly suffer from delayed puberty, anestrus, subestrus, summer infertility, prolonged inter-calving interval and postpartum uterine disorders. Nesfatin-1 and Leptin are directly or indirectly related with body weight (BW), feed parameters and regulation of puberty. The objective of this study was to investigate the influence of Nesfatin-1 and Leptin in pubertal and non-pubertal Murrah buffalo heifers. The Murrah buffalo heifers (n=13) were randomly selected and divided into two groups; pubertal group (PG) and non-pubertal group (NG). Heifers with plasma progesterone (P 4 ) level of ?1 ng/mL were classified as PG. Blood samples were collected at fortnight intervals for analysis of plasma Nesfatin-1, Leptin, P 4 , glucose and non-esterified fatty acids. Body weight, dry matter intake and feed conversion efficiency were recorded at fortnight intervals. The mean (±SEM) plasma Nesfatin-1, Leptin, P 4 , BW and feed conversion efficiency (%) were significantly (P<0.01) higher in PG as compared to NG. Dry matter intake by the heifers was also significantly (P<0.001) higher in PG than NG. Plasma metabolites (glucose and NEFA) did not differ significantly between the groups. The findings of this study suggest that Nesfatin-1 and Leptin have indispensable role in the onset of puberty in buffalo heifers by affecting BW and feed parameters. http://dx.doi.org/10.5455/javar.2015.b107